2019
DOI: 10.3390/universe5090191
|View full text |Cite
|
Sign up to set email alerts
|

Kerr Black Holes within a Modified Theory of Gravity

Abstract: The Kerr black hole is studied within a modified theory of gravity, which adds the effects of vacuum fluctuations near a black hole. These vacuum fluctuations are treated as a dark energy. A parameter is introduced to account for these fluctuations. It is zero for the standard theory and acquires a maximal value, just before there would be no event horizon. The existence of an event horizon not only depends on the value of this parameter, but also on the spin of the black hole. In addition, we study the existe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 48 publications
0
23
0
Order By: Relevance
“…The expression of m ( r ) guaranties that for a > 0 ( a is the Kerr rotational parameter with 0 ≤ a ≤ 1) there is no event‐horizon and only at a = 0 there is still one at r=32m0. This is the latest form as used in pc‐GR (Hess 2019, 2020; Hess & López‐Moreno 2019b). Arbitrary values between 0 and 1 were also considered in Hess & López‐Moreno (2019b)), were the transition from GR and pc‐GR was studied and related to a phase transition.…”
Section: Theorymentioning
confidence: 92%
See 2 more Smart Citations
“…The expression of m ( r ) guaranties that for a > 0 ( a is the Kerr rotational parameter with 0 ≤ a ≤ 1) there is no event‐horizon and only at a = 0 there is still one at r=32m0. This is the latest form as used in pc‐GR (Hess 2019, 2020; Hess & López‐Moreno 2019b). Arbitrary values between 0 and 1 were also considered in Hess & López‐Moreno (2019b)), were the transition from GR and pc‐GR was studied and related to a phase transition.…”
Section: Theorymentioning
confidence: 92%
“…This is the latest form as used in pc‐GR (Hess 2019, 2020; Hess & López‐Moreno 2019b). Arbitrary values between 0 and 1 were also considered in Hess & López‐Moreno (2019b)), were the transition from GR and pc‐GR was studied and related to a phase transition. Other dependencies on r can also be used as can be found in other contributions in this volume.…”
Section: Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…In Boller et al (2019) and Hess et al (2019), the most recent compilation of results on the accretion disks is published, predicting a dark ring followed by a bright one in the light emission of such an accretion disk. In Hess (2019, 2020) and Hess & López‐Moreno (2019), reviews on the theory can be found.…”
Section: Pseudo‐complex General Relativitymentioning
confidence: 99%
“…Dymnikova and Galaktionov [25] consider a model of nonlinear electrodynamics minimally coupled to gravity and study the dynamics of electromagnetic fields of rotating electrically charged black holes. Hess and López-Moreno [26] focus on another model of modified gravity, the so-called pseudo-complex General Relativity and, in this context, they study Kerr black hole in presence of vacuum fluctuations that are determined by the modified gravity model.…”
mentioning
confidence: 99%